The Pedagogical Approach of the Buddha: Analyzing the Buddha’s Teaching Methods Based on Sutta Pitaka - Tri Saputra Medhācitto (Dinasti Publisher, 2024)
Teaching methods are very important elements of learning process, ensuring students not only receive the knowledge but also become attractive and engaged in the learning process. Teaching methods are designed to help the students to understand the teachings easily according to their capacities. This research aims to examine the teaching methods had been adopted by the Buddha as the great spiritual teacher in the world. This research is qualitative research methodology carried out with library approach. The data of the research is mainly based on primary sources which include the Sutta Pitaka and its commentaries, and secondary sources which include the journals, articles, or books written by scholars. Having critically examined the data, this research discovers that the Buddha had used several methods of teaching according to the characters and the capacity of the students. The Buddha examined the audiences’ capacities and their characters before giving the sermon and decide to deliver the teachings by the methods they can understand easily. Looking at the discourses in the Sutta Pitaka, it can be understood that the Buddha had used several methods of teaching such as student-centered method, lecture method, discussion method, narrative method, parable method, gradual method and psychotherapy method.